Земная кора крупных месторождений цветных металлов Болгарии - Йосифов, Д.; Радичев, Р. (Геофизический журнал, 2018)
Розглянуто основні результати досліджень будови земної кори у найбільших рудних районах Болгарії . Панагюрському і Центрально-Родопському. Підтверджено уявлення про її континентальний тип. Доведено наявність розривів поділу Мохо, що різняться значною вертикальною амплітудою (від 7,8 до 13,14 км), які підсилюють і каталізують ендогенні процеси, зокрема рудоутворювальні. Встановлено велику щільність глибинних розривів кори, причому крім відомих мантійних розломів, що обмежують основні поздовжні тектонічні одиниці (Маришський тектонічний шов і Забалканська розломна зона), намічено ще два . Південносередньогірський і Південнородопський. У місцях їх перетину із субмеридіональними рудоконцентрувальними структурами (Панагюрською і Центрально-Родопською) утворилися коромантійні тектонічні вузли, в ареалах яких розміщуються основні рудні поля. Земна кора у досліджуваних рудних районах характеризується градієнтними змінами її глибинної структури . суттєвою тектонічною роздробленістю за масштабами рудоносним потенціалом. The proposed publication explores the main results of the study of the Earth’s crust in the largest ore regions in Bulgaria - Panagyurishte and Central Rhodopes. The concept of its continental type has been confirmed, and the more significant accomplishments can be summarized as follows. À number of ruptures of the Moho boundary, characterized by considerable vertical amplitude (from 7-8 to 13-14 km) have been proven, which facilitate and catalyze the endogenous processes, including ore formation one. A large (unique) density of the Earth’s crust layering in depth has been established. Besides the known mantle faults, limiting the main longitudinal tectonic units (the Maritsa fault zone and the Sub-Balkan fault), two more are identified - the South Sredna Gora and the South-Rhodopes ones. From their intersection with the sub-meridional ore concentrating structures (the Panagyurishte and the Central-Rhodopes ones) core-mantle nods are formed and the main ore fields are located in their ranges. As a whole, the Earth’s crust in the studied ore regions is characterized by gradient changes in its depth structure, represented by large fragmentation, high endogenous permeability, intensive magma saturation and significant ore-bearing potential.